The Promotion of Halal Tourism in Bangka Belitung: The Development of Potential Asset and Local Enterprises Players - Yanasari, Pebri (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
Halal tourism analyses of the development goals often stress the importance of the locality-asset promotion, in which dynamic changes to support the development of potential asset and enterprises players have become driving factors in producing generous well-being outcomes. Challenging such analyses, this article highlights the importance of understanding how locality-based halal tourism contributes to the wider-ranging of reformulated tourism policies in Bangka Belitung. Using a qualitative method, the article investigates the promotion strategy of the development of halal tourism involved the role of policymakers, where the data obtained interviews and documentation. The informants were selected by purposive sampling to understand how halal tourism developed. As it turns out, significant variables expanded in terms of halal tourism's features and advantages, and it is necessary to involve the religious institution driving forces that issued the halal production legality. It is profitable to provide various facilities to support halal tourism development. The collaboration between the Indonesian Ulama Council and the Ministry of Religious Affairs has been significantly affected to arrange reformulated the development of halal tourism to reference local governments to formulate policies in the local context. As an implication, promoting a new tourist destination needs a readjusting of the term halal friendly that implicated business players in managing the tourism industry.